Improvement Of Energy Collection In A Solar System - Syariffah, Othman; Mohd Ruddin, Ab Ghani; Mohamad Rom, Tamjis (Research India Publications, 2016)
Parabolic Dish (PD) one of the Concentrating Solar Power(CSP) technologies, convert the thermal energy in solar radiation to mechanical energy. PD has shown the highest efficiency by nearly 31.25% of solar radiation into electricity and PD has emerged as one of reliable and efficient Renewable Energy (RE) technology. However, to evaluate the PD system performance by using experimental is costly and time constraint. Therefore, a model has become necessary to predict the system performance under Malaysia environment. This paper study on several apparatus such as the size of concentrator, reflective material, type of receiver and using a second concentrator to improvement of energy collection. In this work, a theoretical analysis of a parabolic dish with a secondary concentrator is developed and ray tracing is conducted in order to validate the equations obtained. As a conclusion, by using non-imaging Fresnel lens as a second concentrator, 12 meter of size concentrator, silver as a reflectance material and indirect-illumination receivers (IIR) as a receiver will improve the energy collection in solar system.